Molecular detection and characterization of potato virus Y-NTN and cucumber mosaic virus-S in microtubers and G0 tubers of red and Granola potato - Diky Setya Diningrat; Laela Sari; Ashar Hasairin; Adelia Febriyossa; Heppy Setya Prima; Selvia Dewi Pohan; Larasati Arum Utami (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
This study aimed to detect and molecularly characterize viruses infecting microtubers and G0 tubers of red and Granola potato varieties produced by PT. G10 Agrotechnology, Medan, Indonesia. A total of 50 microtubers and 50 G0 tubers from each variety were collected and tested using serological methods, including enzyme-linked immunosorbent assay (ELISA) and dot immunobinding assay (DIBA), followed by reverse transcription polymerase chain reaction (RT-PCR) and nucleotide sequence analysis. Serological and molecular assays showed that all microtuber samples were free from potato virus Y (PVY), potato virus X (PVX), potato virus S (PVS), and cucumber mosaic virus (CMV). In contrast, G0 tubers were infected by PVY and CMV, whereas PVX and PVS were not detected. The incidence of PVY and CMV reached 80.0% and 82.0%, respectively, in red potato G0 tubers and 28.0% for both viruses in Granola G0 tubers. RT-PCR successfully amplified the coat protein (CP) genes of PVY and CMV, producing fragments of approximately 801 bp and 657 bp, respectively. Sequence and phylogenetic analyses identified the PVY isolates as belonging to the PVY-NTN strain and the CMV isolates as closely related to the CMV soybean stunt strain (CMV-S). These findings indicate that microtubers produced through tissue culture were virus-free, whereas viral infection occurred during the screen-house multiplication stage. The results provide important baseline information for virus monitoring and management strategies to support the production of high-quality potato seed in Indonesia.